Mistakes in the analysis of exotic species establishment: source pool designation and correlates of introduction success among parrots (Aves: Psittaciformes) of the world - Phillip Cassey; Tim M. Blackburn; Kate E. Jones; Julie L. Lockwood (Journal of Biogeography, 2004)
Aim To evaluate the effect of mis‐specifying the correct comparison of species pools in the study of species characteristics associated with the biological introduction of exotic species. Methods We use a high quality data set on biological introductions of parrots (Aves: Psittaciformes). These data allow us to examine relationships between life history traits and probability of successful transition through an introduction stage when the species pool is both correctly and incorrectly specified. Results For the establishment of introduced parrot species, nearly half of the predictor variables showed different patterns of significance when an incorrect pool was specified. Multivariate analysis identified entirely different sets of variables as independent predictors of establishment success, depending on the species pool used. Correct pool specification identified that introduced parrot species have been more likely to establish if they have broader diets and are more sedentary. Main conclusions Conclusions from the analysis of biological introductions are likely to depend on the specification of the species pool for such analyses. In the analysis of parrot introductions, this was particularly apparent in establishment success following release. Further studies that analyse the introduction pathway need to examine the effects of pool mis‐specification so that the generality of our results can be assessed.